Methylation Pathways and SARS-CoV-2 Lung Infiltration and Cell Membrane-Virus Fusion Are Both Subject to Epigenetics - Pruimboom, Leo (Frontiers in cellular and infection microbiology, 2020)
The recent pandemic SARS-CoV-2 outbreak affects all kinds of individuals worldwide. The health, social, and economic impacts of the pandemic are dramatic, and vaccines or specific treatment options are not yet available. The only approaches that we currently have available to stop the epidemic are those of classical epidemic control, such as case isolation, contact tracing and quarantine, physical distancing, and hygiene measures. It is therefore essential to find further preventive measures and possible interventions that can slow down the number of infected individuals and decrease the severity of disease when affected by SARS-CoV-2. It seems that epigenetic mechanisms are an important part of the pathophysiology and illness severity of COVID-19. These mechanisms have been identified in SARS-CoV-2 but also in other viral infections. If and when these mechanisms are confirmed, then epigenetic interventions influencing DNA methylation could be indicated as primary and/or secondary preventive options.